What kind of secular education? Ideals and politics of Fernando de los Ríos (Foro de Educacion, 2018)
«What kind of secular education? Ideals and politics of Fernando de los Ríos». Socialist politician of the first half of the twentieth century in Spain stands out for an intellectual trajectory made in the Institution Libre de Enseñanza (ILE). In the progressive biennium in the Second Republic, as Minister of Justice and later as Minister of Public Instruction, he had the opportunity to realize Krausoginerist, neo-Kantian and socialist ideals. He promoted separation between State and Catholic Church and religion freedom. In education matter, he prompted the construction of more than 6,000 schools under the so-called «Unique School» model (Einheitschule) referring to an ideal of a school as a whole, coherent, integrated, equalizing and systematic (P. Natorp). Within this framework, the secular school, the suppression of the Catholic religion and the elimination of the teaching carried out by the Church, in particular by religious orders, were strongly promoted. It was a question of proceeding to the revolution of the consciences: to free the conscience of the child from all confessional meddling. The Catholic sectors were mobilized in front of that policy that they considered extremely aggressive against the Church. Conflict what was called the «school war». But, was De los Rios’s objective a school without or against religion – or was it a neutral school, therefore, opened to the religious sense and to the knowledge of different religions, as Giner put it? We certainly have a crucial theme in the feasibility problems of the Second Republic.